Risk assessment in ensuring aircraft on-board systems safety - H. E. Fourar; B. D. Ogunvoul; V. D. Budaev; F. Lachi (Научный вестник МГТУ ГА, 2020)
A method of risk assessment of an aircraft on-board information system is being considered, which allows ensuring reliability and safety of such a complex system in operation. This technique implies application of combined mathematical tools to estimate the risks that complex systems/items are being exposed to. The existing risk assessment methods are not flexible enough to solve the complex task of enhancing comprehensive safety of an aircraft information system (AIS) due to difficulty in unifying the criteria for estimating the degree of hazard in reference to all safety concepts. Currently, risks severity and mechanism for the development of one undesirable event (risk event) into more complex forms during technical operation of an aircraft items/system are not being considered. However, the method proposed in this article intends to become a catalyst for generation of new criteria on a unified basis for estimating safety of such a technical complex system such as AIS, since it contains three-component risk parameters. I.e. the risk for threats from violators (cases of unlawful interference (UI)), vulnerabilities (functional hazards that contribute to UI and its development in a system) and loss (set of criteria that evaluates consequences of UI). As a result, these criteria and parameters of threecomponent safety will allow us to find a new approach to determining the complex risk to which important aircraft systems, such as on-board aircraft information systems, are exposed. This article presents a method for determining risk that takes into account the three-component safety concept. Together, these components will make it possible to evaluate technical systems hazard degree, taking into account their sophistication. The information provided in this paper by the authors is a scientific hypothesis designed to draw attention of the scientific community to the problem of lack of methods for evaluating multicomponent risks in such a system as AIS. The article presents the basic criteria for evaluating a complex three-component risk; they are not sufficient for the full formation of new criteria for evaluating the safety of a complex aircraft system/item and requires clarification of their parameters. Thus, this work is not absolute as a complete solution to the complex problem of enhancing comprehensive safety of AIS, but only offers a methodology for unifying the three safety components to evaluate complex risk.